Coagulation Status and Surgical Approach as Predictors of Postoperative Anemia in Patients Undergoing Thoracic Surgery: A Retrospective Study - Lang, Zhongping; Wu, Yue; Bao, Minwei (Frontiers in Surgery, 2021)
Objective: Postoperative anemia is a common complication after a major surgery. Our study aims to identify factors that are associated with higher risk of developing postoperative anemia after thoracic surgery. Methods: We conducted a retrospective study of 465 patients who underwent pulmonary surgery in 2017 in Shanghai Pulmonary Hospital, China. Of them, 191 patients underwent standard open thoracotomy (OT), and 274 patients underwent video-assisted thoracic surgery (VATS). A total of 350 patients were diagnosed with postoperative anemia, and 115 patients did not have anemia. Multiple logistic regression was used to compute odds ratios for predicting preoperative anemia. Results: Postoperative anemia was associated with significantly lower weight (p < 0.001) and height (p = 0.022) of the patients, as well as higher prothrombin time (PT), and international normalized ratio (INR) (p = 0.012). Open thoracotomy resulted in a 1.2-fold increase in the incidence of postoperative anemia compared to VATS (p = 0.002). Multiple logistic regression analysis identified INR [OR (95% CI) 24.46 (2.05–292.27; p = 0.012] and surgical approach [OR (95% CI) 0.48 (0.31–0.74); p < 0.001] as predictors of postoperative anemia and postoperative drop in hemoglobin (Hb). Conclusion: Postoperative coagulation status and surgical approach are statistically significant predictors of postoperative anemia in patients undergoing thoracic surgery. International normalized ratio and surgical approach are specifically associated with Hb drop immediately after the surgery.